Relational ethics in palliative care research: including a person-centred approach - Haraldsdottir, Erna (Palliat Care Soc Pract, 2019)
The traditional approach to research ethics is to ensure that all ethical issues are adhered to through the scrutiny of research proposals by research ethics committees, themselves sitting within national research governance frameworks. The current approach implies that all potential ethical issues can be considered and mitigated prior to the research. This article is a perspective piece whereby we consider how this approach, on its own, is not enough to ensure ethical practice. We draw attention to the limitations of current ethical procedures in the inherent detachment between the researcher and research participants. We argue that applying a person-centred approach to research ethics allows for contextual and situational factors and places the relationship between research participants and researcher as central.